Wasp venom and acute kidney injury: The mechanisms and therapeutic role of renal replacement therapy. (May 2019) - Gong, Jianhua; Yuan, Hai; Gao, Zhao; Hu, Fengqi
Abstract: Stinging accidents involving wasp venom are a notable cause of acute kidney injury (AKI) in Asia. However, very little attention has been paid to the understanding of the mechanisms involved in this type of AKI. The aims of this review are to explore the evidence for the mechanisms and the therapeutic role of renal replacement therapy of wasp venom and AKI. A systematic literature search was conducted using PubMed for the association among wasp venom and AKI. Wasp venom is a complex mixture of biologically active components, including enzymes, amines, and peptides. Wasp venom may induce local anaphylaxis reactions as well as systemic reactions such as AKI. AKI may develop as a result of direct nephrotoxic effects of the venom or secondary intravascular hemolysis and/or rhabdomyolysis. Histopathological features of renal biopsies predominantly include acute tubular necrosis and acute interstitial nephritis. Renal replacement therapy, which includes intermittent hemodialysis, hemoperfusion, plasmapheresis, continuous renal replacement therapy, and peritoneal dialysis, has been used to treat severe AKI cases induced by wasp stings. Continuous renal replacement therapy appears to provide more benefit than intermittent hemodialysis in the treatment of wasp sting-induced AKI. In this review, we summarize the existing evidence of the mechanisms and treatment for venom-induced AKI, with a particular emphasis on the role of renal replacement therapy in the management of severe AKI following massive wasp stings.